STRATEGI GURU DALAM PENERAPAN MATERI KEMAMPUAN BERNALAR KRITIS PADA PEMBELAJARAN ANAK USIA 5-6 TAHUN - Dea Putri; Rizki Surya Amanda; Uswatul Hasni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
ABSTRACT This research was motivated by preliminary observations showing that the critical reasoning skills of 5-6 year old children are still developing in various ways. This study aims to determine the strategies used by teachers in the critical reasoning skills material applied in the learning of 5-6 year old. This research uses a qualitative approach with a descriptive type. Data collection techniques through interviews, observation, and documentation. Data analysis uses data reduction, data presentation, and drawing conclusions, while data validity is tested by triangulation of sources and techniques. The results show that teachers' strategies are carried out in a planned manner through active and creative learning, such as playing, experiments, role-playing, discussions, questions and answers, habituation, group work, and reinforcement in the form of praise and stickers. This strategy encourages children to be more active in asking questions, expressing opinions, working together, and solving simple problems even though their development still varies. Thus, teacher strategies play a significant role in stimulating critical reasoning skills in 5-6-year-old children at Pertiwi II Kindergarten in Jambi.